Talc-containing decorative material for glass ceramic articles
By adding talc to glass ceramic enamel, the problems of enamel tend to be mottled and peeled are solved, and high-quality preparation of black enamel is achieved, reducing the production complexity and cost.
Patent Information
- Application Number
- CN202380057176.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-07-28
- Publication Date
- 2025-03-14
AI Technical Summary
Existing glass-ceramic enamels are prone to become mottled when used, and they are poorly cleaned of food sediments, resulting in peeling problems. The commonly used black enamel preparations require special processing, which increases cost and complexity.
Talc is incorporated into the enamel composition, and black enamel that is not easily mottled is obtained by firing, and the crack resistance and wear resistance of the enamel are improved by adjusting the ratio and particle size of the glass frit and talc.
Black enamel that is not easy to change mottled during use is realized, which improves crack resistance and wear resistance, and reduces preparation complexity and cost.
Smart Images

Figure CN119630616A_ABST
Abstract
Description
[0001] The present invention relates to the field of glass ceramics. More precisely, it relates to glass ceramic articles particularly intended to cover or receive heating elements and / or intended to serve as furniture surfaces (optionally in combination with heating elements). An example of such an article is a hob, an oven door, a fireplace insert, a firewall, or a central island in a kitchen or dining room.
[0002] A glass-ceramic article is defined as an article based on a glass-ceramic material substrate (such as a glass-ceramic plate) which may be equipped with accessories or additional decorative or functional elements. The article may refer to the substrate alone or to the substrate with additional equipment. For example, the article may represent a stove equipped with a control panel and / or a heating element. Prior art
[0003] There are several commonly used glass ceramic products, in particular glass ceramic cooktops, which have proven very popular among homeware retailers, appliance manufacturers and end users. This success can be explained in particular by the attractive appearance of these cooktops and their ease of cleaning.
[0004] Glass ceramics are initially glasses, called precursor glasses, mother glasses or "green-glasses", whose specific chemical composition enables controlled crystallization to be induced by appropriate heat treatments (called ceramizing processes). This specific partially crystalline structure gives glass ceramics their unique properties.
[0005] There are currently different types of glass-ceramics, each variant being the result of significant research and many experiments, since it is difficult to modify these plates and / or the methods for obtaining them without the risk of adversely affecting the desired properties.
[0006] In particular, for use as a cooking stove, the transmittance of a glass ceramic stove in the visible wavelength range must generally be both low enough to mask at least a portion of the underlying heating element in the switched-off state, and high enough so that, depending on the type of heating, the user can visually detect the heating element in operation for safety purposes. A glass ceramic stove must have a high transmittance in the infrared wavelength range, in particular in the case of radiant hobs. It must also have a mechanical strength that is sufficient for the field of application of such stoves. In particular, in order to be suitable for use as a stove, a glass ceramic stove must have good pressure resistance as defined in EN 60335-2-6, as well as impact resistance.
[0007] The most common glass ceramic hobs are dark in color, especially black or brown or brownish orange. They are usually decorated with enamel on the top to define the cooking area and function keys, and to protect the glass ceramic from wear and tear. The use of black enamel is particularly attractive because it provides a low contrast appearance with the black glass ceramic hob.
[0008] Enamel is typically a mineral layer formed by firing an enamel composition comprising glass frit and pigments.
[0009] Therefore, enamels have much higher heat resistance, wear resistance, chipping resistance and chemical resistance than conventional decorative elements (such as paint), which enables them to be used in glass ceramic products, especially stoves.
[0010] However, enamel coloring based on commercially available black pigments such as spinel CoCrFeNi or CuCr brings a tint that tends towards brown. Moreover, for patterned decorations, these enamels are likely to streak after cleaning the plate with a dry cloth. These disadvantages are particularly evident in enamels formulated with DEC 146 glass frit as described in FR 2 701 473 A1.
[0011] Furthermore, the accumulation of food deposits on the enameled glass ceramics leads to flaking of the enamel under the action of temperature, in particular for enamels formulated with DEC 146 frit, and more particularly for enamels made with IB2 frit as described in application FR 3012130A1.
[0012] Document FR 2457312A1 describes a self-cleaning coating composition, in particular for the inner walls of ovens, comprising an oxidation catalyst, an oil and grease inhibitor and a binder, wherein the action of the oxidation catalyst enables self-cleaning by volatile oxidation of the oil and grease on the oven walls. According to this document, the oil and fat inhibitor is able to reduce the temperature at which self-cleaning occurs. Talc is one of these inhibitors. Thus, this document does not take into account any particular aspects associated with the use of talc in the enamelling of glass ceramic plates, such as the desired mechanical properties or aesthetic considerations, in particular in terms of color.
[0013] Document FR 2858974A1 addresses the problem of the brown color of enamels based on black pigments. According to the document, this coloration is due to the presence of zinc oxide in the flux, which reacts chemically with the surface of the commercially available black pigment during firing. To solve this problem, the document proposes the use of enamels based on colorless glass frit and a glass-coated black pigment in a weight proportion of 0% to 10%. However, the disadvantage of this solution is that it requires special processing techniques, making the enamel manufacturing method more complicated and bringing additional costs.
[0014] There remains a need for readily available enamel compositions for glass-ceramic ware having a black colour and satisfactory mechanical properties, in particular the resulting enamels do not become mottled when used, for example on contact with the nail or a dry cloth, and allow food deposits to be cleaned with reduced flaking. SUMMARY OF THE INVENTION
[0016] The object of the present invention is to meet these needs by providing such an enamel composition.As can be seen herein, the inventors have demonstrated that the incorporation of talc into an enamel composition enables a black enamel to be obtained which does not become mottled in use and which offers improved resistance to cracking.
[0017] From a tribological point of view, the invention is quite surprising since talc has a very low hardness compared to pigments commonly used in enamels, for example.
[0018] Talc also has the advantage that it is an abundant and inexpensive raw material.
[0019] This solution can be easily transferred to existing enamel formulations as it does not require any significant changes to the enamel manufacturing process nor does it involve any significant cost increase.
[0020] Thus, according to a first aspect, the present invention relates to an enamel composition for glass-ceramic articles comprising glass and talc.
[0021] The enamel composition may represent the enamel before and after firing. Therefore, in the enamel composition according to the present invention, the term "glass" refers to the glass frit before firing, and the glass matrix obtained by melting the glass frit after firing. The enamel according to the present invention is usually obtained by firing at a temperature higher than 850°C, preferably higher than 900°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Other features and advantages of the invention will become apparent from the following description given with reference to the accompanying drawings, which illustrate exemplary embodiments of the invention without any limiting nature. In the drawings:
[0024] Figure 1 is a colorimetric diagram giving data related to Examples 1 to 4 according to the invention and Comparative Examples 1 and 2. The diagram comprises two parts: a first part in two dimensions according to the colorimetric coordinates a* and b*, which is schematically divided into 4 color gamuts (yellow, red, blue and green), and a second part in one dimension, which is represented by the L* coordinate of the sample, representing the lightness of the sample color, i.e. the closer the L* is to 0, the darker the sample appears.
[0025] Figure 2 Photographs showing samples of enamel-coated glass-ceramic panels illustrating the scores 0, 2 and 4 of the so-called "nail mark" test explained in the examples of the present application.
[0026] Figure 3 The results obtained for Examples 1 to 4 according to the invention for the same test are shown.
[0027] Figure 4 Photographs showing Comparative Example 3 and Example 5 according to the present invention after the peeling test described in the examples of the present application are shown.
[0028] Description of embodiments of the invention
[0029] In a particular embodiment, the enamel composition according to the invention comprises glass frit and talc. According to this embodiment, the composition according to the invention may further comprise an organic medium.
[0030] The organic medium enables the desired viscosity to be set for application to the substrate and enables bonding to the substrate. This medium is selected to ensure good suspension of the particles (glass frit and talc) and must be consumed at the latest during the enamel firing process, and can be any medium or organic binder commonly used in conventional enamel compositions and can especially contain solvents, diluents, oils such as pine oil and other vegetable oils, resins such as acrylic resins, petroleum fractions, film-forming substances such as cellulosic materials, etc.
[0031] In particular, the organic medium suitable for the present invention may contain at least one compound selected from glycols and pine oil. Preferably, the organic medium contains at least one glycol, such as 2-(2-butoxyethoxy)ethanol or 2-butoxyethanol.
[0032] The proportion of the medium in the composition to be deposited may be between 40% and 60% by weight of the composition, preferably between 45% and 55% by weight. Thus, the enamel composition before deposition onto the glass-ceramic substrate is generally in the form of a stable liquid-solid mixture with a pasty consistency, the viscosity of which is suitable for deposition methods, in particular for screen printing.
[0033] In another embodiment, the enamel composition according to the invention comprises a glass matrix and talc.
[0034] The composition according to the invention may comprise talc in a proportion of 5% to 40% by weight, in particular 7% to 35% by weight, preferably 10% to 30% by weight, relative to the total weight of the enamel.
[0035] The composition according to the invention may comprise less than 1% by weight of pigments, for example less than 0.5% by weight, in particular less than 0.1% by weight of pigments, relative to the total weight of the enamel, and the enamel is preferably free of pigments.
[0036] In this way, the present invention can simplify the enamel composition, because the black enamel can be obtained by simply mixing glass frit and talc without adding pigments.However, conventional black enamel formulations may require the use of additional pigments in addition to black pigments to compensate for certain color shades.
[0037] The enamel composition according to the invention can be obtained from a mixture of glass frit and talc having a D90 of less than 20 μm, in particular less than 15 μm, preferably less than 10 μm.
[0038] That is to say, in this case, 90% of the particles constituting the mixture of glass frit and talc have a diameter of less than 20 μm, in particular less than 15 μm, preferably less than 10 μm.
[0039] As demonstrated in the examples below, the inventors have observed that a reduction in the diameter (i.e., particle size) of the particles constituting the mixture enhances the effect of the invention. In this way, an enamel composition comprising glass frit and talc having a fine particle size as described in the previous paragraph can achieve darker enamel colors and less prone to marking enamels than an equivalent enamel composition having a higher particle size.
[0040] Furthermore, such a fine particle size also enables a higher wear resistance of the enamel to be achieved than is observed for an equivalent enamel composition having a higher particle size.
[0041] In a particular embodiment of the invention, the composition according to the invention comprises a glass having the following composition:
[0042] SiO2: 35-50%
[0043] B2O3: 23-30%
[0044] Al2O3: 10-22%
[0045] Li2O: 1-3%
[0046] Na2O: 0-3%
[0047] K2O: 2-5%
[0048] Li2O+Na2O+K2O:<8%
[0049] CaO: 1-5%
[0050] CaO+MgO+ZnO+BaO+SrO:<7%
[0051] TiO2: 0-2%
[0052] ZrO2: 0-5%
[0053] These proportions are expressed as weight percent relative to the total weight of the glass.
[0054] Such a glass composition corresponds to the glass frit known as "DEC146" and is described in application FR 2 701473 A1. For the enamel composition according to the invention containing the glass composition as described above, the addition of talc improves in particular the resistance to marking of the enamel, among the effects of the invention described above.
[0055] According to this embodiment, the glass may have a thickness less than or equal to 60×10 -7 K -1 , especially less than or equal to 56×10 -7 K -1 The coefficient of thermal expansion.
[0056] Also according to this embodiment, the glass may have a softening point T above 650° C., in particular above 680° C. L .
[0057] According to this embodiment as well, the composition according to the invention may comprise talc in a proportion of 15% to 40% by weight, in particular 17% to 35% by weight, preferably 20% to 30% by weight, relative to the total weight of the enamel.
[0058] In another embodiment of the present invention, the enamel composition comprises a glass of the following composition, these proportions being expressed as weight percentages relative to the total weight of the glass:
[0059] SiO2 45-60%, preferably 50-58%,
[0060] Al2O3 12-22%, preferably 15-19%,
[0061] B2O3 12-22%, preferably 15-19%,
[0062] Li2O 0-5%, preferably >0-5%,
[0063] Na2O0-2%,
[0064] K2O>2%,
[0065] CaO 0-4%, preferably 0-2%,
[0066] MgO 0-4%, preferably >0-4%,
[0067] ZnO 0-4%, preferably >0-4%,
[0068] BaO 0-4%, preferably >0-4%,
[0069] ZrO2 0-4%, especially 0-2%, preferably >0-2%
[0070] TiO2 0-1%, preferably 0-0.5%,
[0071] And the total proportion of oxides
[0072] CaO+MgO+BaO+SrO+ZnO
[0073] Less than or equal to 10%, preferably between 2% and 8%.
[0074] Such a glass composition corresponds to the glass frit known as "IB2" and is described in application FR 3012130A1. For the enamel composition according to the invention containing the glass composition as described above, the addition of talc improves in particular the spalling resistance of the enamel, among the effects of the invention described above.
[0075] According to this embodiment, the composition according to the invention may comprise talc in a proportion of 5% to 30% by weight, in particular 7% to 20% by weight, relative to the total weight of the enamel, the enamel preferably comprising talc in a proportion of 10% to 20% by weight.
[0076] According to a second aspect, the invention relates to a process for obtaining an enamel composition according to the invention, comprising mixing glass frit and talc and optionally attrition of the resulting mixture for a period of 5 minutes to 1 hour, in particular 15 minutes to 45 minutes, preferably 20 minutes to 40 minutes.
[0077] "Grinding" means comminution by grinding using a mill or micromill, in particular in an alcoholic medium. An example of such a micromill is the micromill sold under the reference "Mill PE075" by the company Netzsch.
[0078] Grinding enables the mixture of glass frit and talc particles to be reduced to a known particle size, in particular to obtain a D90 of less than 20 μm, in particular less than 15 μm, preferably less than 10 μm.
[0079] According to a third aspect, the invention relates to a glass-ceramic article comprising at least one substrate, such as a glass-ceramic plate, which is at least partially coated with an enamel composition according to the invention.
[0080] The substrate is usually a board, particularly intended to:
[0081] for use with at least one light source and / or heating element, in particular covering or receiving at least one light source and / or heating element, or
[0082] Use as furniture surfaces or fireplace inserts.
[0083] The substrate generally has a shape selected from the group consisting of: rectangular, in particular square, circular and oval. It generally has:
[0084] the face that faces the user in the use position, called the visible face or outer face, which may correspond to the upper face in the use position,
[0085] A second face opposite to the outer face, called the inner face, which is usually concealed in the use position, for example in a furniture frame or a cabinet, and which may correspond to the lower face in the use position,
[0086] Edge, or thickness.
[0087] The upper or outer surface is generally flat, but may also locally have at least one raised area and / or at least one recessed area and / or at least one opening and / or a chamfered edge. These shape changes may constitute a continuous change in the plate.
[0088] The lower or inner surface may also be flat and smooth, or have a teardrop shape.
[0089] The thickness of the glass ceramic substrate is generally at least 2 mm, in particular at least 2.5 mm, advantageously less than 15 mm, in particular 3 to 15 mm, in particular 3 to 8 mm or 3 to 6 mm.
[0090] The substrate may be based on any glass ceramic and advantageously has a coefficient of thermal expansion (CTE) of zero or almost zero, in particular less than (in absolute terms) 30×10 -7 K -1 , especially below 15×10 -7 K -1 , or even less than 5×10 -7 K -1 .
[0091] In particular, a black or brown substrate is used which can, in combination with a light source placed underneath, display a luminous area or a decoration while masking any underlying elements. In particular, it can be based on a black glass-ceramic comprising crystals with a β-quartz structure within a residual glass phase, the absolute value of the thermal expansion coefficient of which is advantageously less than or equal to 15×10 -7 K -1 , or even 5×10 -7 K -1 , such as the glass ceramic panels sold by Eurokera under the name Kerablack+.
[0092] It can in particular be an arsenic-refined glass-ceramic having a composition as described in patent applications EP0437228 or US5070045 or FR2657079, or a tin-refined glass-ceramic having an arsenic oxide content of preferably less than 0.1%, as described, for example, in patent application WO2012 / 156444, or a sulfide-refined glass-ceramic as described in patent application WO 2008 / 053110.
[0093] If desired, the substrate may be coated with other functional and / or decorative coatings or layers, which are deposited in particular in areas outside the areas coated with the enamel according to the invention, such as an opacifying paint layer based on a common pattern of other enamels or on another part of the substrate, or at least one functional layer such as an anti-scratch layer, an anti-splash layer, an opacifying layer, etc.
[0094] The article according to the invention may further comprise at least one light source and / or at least one heating element associated or combined with the substrate, chosen from radiant or halogen elements, atmospheric gas burners and induction heating means.
[0095] The light sources may be integrated into or coupled to at least one display unit structure, an electronic control panel with touch-sensitive controls, a digital display, etc. These light sources are advantageously formed by a display consisting of light-emitting diodes spaced apart to a certain extent, which are optionally associated with at least one light guide.
[0096] The article according to the invention may also be combined with at least one additional functional element, such as a frame, a connector, an electrical line or a control element.
[0097] In particular, the article according to the invention has good thermal resistance compatible with the use of various types of heaters and does not cause problems of maintenance, scratching or wear as previously mentioned, in particular compared to glass-ceramic articles comprising typical enamels.
[0098] According to a fourth aspect, the present invention relates to a method for obtaining a glass-ceramic product according to the present invention, comprising:
[0099] a. Provide glass ceramic substrate,
[0100] b. printing on the substrate, in particular screen printing the enamel composition according to the present invention,
[0101] c. ceramicizing the assembly of the substrate and the enamel,
[0102] In particular, the ceramizing step comprises heating the combination of the substrate and the enamel at a temperature of 650° C. to 830° C., preferably for 5 to 90 minutes, and then at a temperature of 850° C. to 1100° C., preferably for 5 to 30 minutes.
[0103] The manufacture of glass ceramic plates is usually carried out as follows: a glass having a composition selected for forming glass ceramics is melted in a melting furnace, the molten glass is then rolled into a standard strip or sheet by passing the molten glass between rollers, and the glass strip is cut into the desired size. The plate cut in this way is decorated with an enamel-based decorative material applied by screen printing or enamel spraying, and then ceramicized in a manner known per se. Ceramics consists in firing the plate according to a selected thermal profile to convert the glass into a polycrystalline material known as glass ceramics, which has a zero or almost zero coefficient of expansion and can withstand thermal shocks up to 700°C. Ceramics generally include a gradual temperature increase step, for example, up to a "nucleation platform" temperature of 650°C to 830°C, which can last for 5 to 90 minutes. The temperature is then raised again to allow the crystal to grow, until, for milky and opaque glass ceramics, for example, a so-called "crystal growth platform" temperature of 850°C to 1100°C, preferably 900°C to 1000°C, which is maintained for example for 5 to 30 minutes. Finally, the plate is rapidly cooled to room temperature.
[0104] Where appropriate, the method also comprises a cutting operation, for example using a water jet, or by mechanical cutting using a cutting wheel, followed by a shaping operation, for example by grinding or beveling. Preferably, this cutting operation is carried out before ceramization.
[0105] The enamel is deposited on the glass ceramic substrate before ceramization. This deposition is carried out by printing, for example digital printing or screen printing.
[0106] The screen printing method consists in depositing a pasty liquid through the meshes of a screen printing mesh onto a glass sheet, in particular using a squeegee. The holes of the screen are blocked in the portions corresponding to the areas of the glass sheet that are not to be coated, so that the paste can only pass through the screen in the areas to be printed according to a predetermined design. The selective blocking of the holes is thus carried out according to the negative of the design to be printed.
[0107] This selective sealing is usually performed by applying a photo-crosslinkable resin to the screen and then irradiating the portions of the screen to be sealed with ultraviolet radiation.
[0108] Selective exposure is achieved, for example, by means of LEDs emitting ultraviolet radiation, which are controlled by a computer to block the mesh to match the selected image file.
[0109] The mesh size of the screen is chosen as a function of the viscosity and the surface tension of the paste and as a function of the desired thickness of the layer deposited by screen printing.
[0110] The following examples are representative of the present invention described above, but are not intended to be limiting thereof. Example
[0111] The following examples illustrate the results obtained with glass-ceramic articles and enamels according to the invention (Examples 1 to 8) compared with reference examples (Comparative Examples 1 to 4) relating to different previous glass-ceramic articles and enamels. The composition of the enamels contained therein is described in detail in the following Tables 1 and 2, in which the content of each compound is expressed as a percentage by weight relative to the total weight of the enamel. The enamels were tested on two different types of glass frit: DEC 146 as described in application FR 2701473A1 and IB2 as described in application FR3012130A1. For IB2, two different glass frit particle sizes were tested.
[0112] [Table 1]
[0113]
[0114] [Table 2]
[0115]
[0116] Tables 1 and 2 also show several parameters specific to enamels which are obtained and described in detail below.
[0117] For each example, a mixture between glass frit and pigment or talc was prepared. If necessary, this mixture was then ground using an attrition microgrinder ("Mill PE075" from Netzsch) in an alcohol medium containing zirconium oxide beads with a diameter of 1 mm (reference "Zetabeads Plus" from Netzsch).
[0118] The particle size of the resulting mixture, whether ground or not, is then measured using a laser particle size analyzer reference "Mastersizer 3000" from Malvern.
[0119] The mixture was then screen printed onto Kerablack+ mother glass from Eurokera SNC and fired at 930°C in a ceramics cycle.
[0120] The colorimetric parameters L*, a* and b* defined in the CIE colorimetric system were evaluated in a known manner by reflectance colorimetry using a Byk-Gardner Color Guide 45 / 0 colorimeter.
[0121] All colorimetric data from Examples 1 to 4 according to the invention and Comparative Examples 1 and 2, all containing DEC146 glass frit, are also shown in Figure 1 's color diagram.
[0122] Comparative Examples 1 and 2, which contain black and blue pigments, both exhibit a brown colorimetric trend, ie, an a* coordinate greater than 0.7, which is particularly pronounced for Comparative Example 2.
[0123] Examples 1 to 4 containing the same glass frit as Comparative Examples 1 and 2 but without pigment have a* coordinates between 0 and -0.3 with small variations based on the amount of talc and their particle size to make the brown tint weaker than the enamels in Comparative Examples 1 and 2.
[0124] Similarly, the b* coordinates of Examples 1 to 4 according to the invention are stable, between -3.53 for Example 1 and -4.04 for Example 2, with grinding appearing to cause a slight shift towards a bluer hue colorimetrically.
[0125] Finally, grinding affects the brightness of the enamel. In particular, comparing Examples 1 and 2 or 3 and 4, a reduction in the L* coordinate can be observed in the case where grinding has been carried out. This effect is more pronounced for Example 4, which has a glass frit / talc ratio of 80 / 20.
[0126] The enamel compositions according to the invention thus enable satisfactory dark shades to be obtained, in particular when they have a D90 of less than or equal to 10 μm and / or a talc content of 20% by weight relative to the total weight of the enamel.
[0127] For enamel compositions containing IB2 frit, Comparative Examples 3 and 4 made with 100% IB2 frit have a neutral black tint. The advantage of Examples 5 and 6 to 8 is that their colorimetry is very close to the talc-free compositions to which they are referenced, namely Comparative Examples 3 and 4, respectively.
[0128] Tables 3 and 4 below show the tests performed on each of the above compositions.
[0129] [Table 3]
[0130] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Rt(μm) 4.0±0.4 2.7±0.5 1.2±0.2 2.2±0.4 Ra(μm) 0.31±0.02 0.23±0.01 0.11±0.01 0.26±0.03 60° glossiness 37.3 44.0 88.0 69 Nail mark test 2 2 0 0 Flaking 2.5 - 4 3
[0131] [Table 4]
[0132] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Rt(μm) 5.6±0.5 2.5±0.2 6.2±0.4 1.9±0.3 1.2±0.4 1.5±0.2 3.1±0.4 1.3±0.4 Ra(μm) 0.74±0.04 0.24±0.03 1.80±0.05 0.16±0.02 0.12±0.02 0.14±0.01 0.28±0.02 0.13±0.01 60° glossiness 33.4 60.1 51.0 83.0 88.0 81.0 32.0 78.0 Nail mark test 1 0 1 0 0 0 1 0 Flaking - 2 - 1 1 - 1 2
[0133] The measurements of total roughness Rt and average roughness Ra were obtained using a Mitutoyo Sj-400 roughness tester according to ISO 97 standard at 5 points on a 5 cm square flat area screen printed on a 9×9 cm substrate over an evaluation length of 4 mm.
[0134] Gloss measurements at 60° were performed using a Byk-Gardner Spectro-Guide 45 / 0 Gloss colorimeter according to ISO 2813. The results of these measurements are expressed in gloss units (GU). The higher the gloss value, the more glossy the sample is observed to be. Conversely, lower values represent the dullness of the sample.
[0135] In general, a decrease in particle size in talc-based enamels results in an increase in gloss and a decrease in roughness.
[0136] The samples were also subjected to a "nail mark" test performed on an enamel plate completely covering the glass ceramic substrate. This test involves scratching with the index fingernail over a distance of 5 cm. The samples were then rated from 0 to 4 based on the mark left on the enamel. A score of 0 represents an enamel with no marks at all, while a score of 4 represents an enamel with very noticeable marks. Figure 2 Photographs showing representative samples labeled 0, 2, and 4. A score of 0 or 1 meets consumer expectations regarding the susceptibility of the enamel to marks (eg, rag marks). Figure 3 The results obtained for Examples 1 to 4 according to the present invention are shown.
[0137] It can thus be seen that comparative enamels 1 and 2 have a score of 2, which is considered unsatisfactory, whereas the talc-based enamels of Examples 1 to 4 containing the same glass frit have a lower score of 1 or even 0 for the enamels in which the mixture of glass frit and talc has been ground (Examples 2 and 4). The presence of talc in these enamels means that they perform better in terms of trace sensitivity.
[0138] With regard to the enamels containing IB2 frit, those of comparative examples 3 and 4 already have satisfactory ratings. It should therefore be pointed out that the addition of talc enables satisfactory trace sensitivity to be maintained.
[0139] The results given above also demonstrate that the talc content has little influence on the trace sensitivity of the enamel, since equivalent results were obtained for Examples 1 and 3 (20% and 30% by weight of talc, respectively), 2 and 4 (20% and 30% by weight of talc, respectively) and 6 and 8 (10% and 20% by weight of talc, respectively) according to the invention.
[0140] Furthermore, as can be seen by comparing Examples 1 and 2 or 3 and 4 according to the invention, the reduction in particle size brought about by grinding provides for better performance of the talc-containing enamel in terms of trace sensitivity.
[0141] The peeling test simulates the cleaning of burnt food accumulated on the glass ceramic stove decorated with enamel. It is carried out on the inductor heating area, and includes placing a mixture of different foods (ground beef, cheese, sugar, eggs, milk, flour, ketchup, corn starch, salt, pepper) on the enamel of the heating area, and burning it for 10 minutes at a power corresponding to a hot spot of 420°C. The hot spot is the average value of the measurement performed using a thermocouple placed on the bottom of the pan after the pan has been removed from the glass ceramic product and a thermal imager at the top. This step is repeated 5 times. After the first and fifth cycles, a scraper, non-abrasive pad and glass ceramic cleaning product are used to clean the glass ceramic surface. The enamel peeling degree is then observed, and the sample is scored as 0 (no peeling) to 5 (peeling on the entire test surface).
[0142] Figure 4 The results of the peeling tests of Comparative Example 3 and Example 5 according to the present invention are shown.
[0143] When comparing:
[0144] According to Examples 2 and 4 of the present invention and Comparative Example 1,
[0145] According to Example 5 of the present invention and Comparative Example 3,
[0146] According to Examples 7 and 8 of the present invention and Comparative Example 4,
[0147] The addition of talc to the glass frit in the enamel brings about improved chipping resistance.
[0148] In particular, as observed in Examples 5, 7 and 8, the chipping resistance of the enamels containing IB2 glass frit shown in Comparative Examples 3 and 4 is significantly improved by the addition of talc.
[0149] The wear resistance of the enamel according to the invention was also tested according to two protocols reported as "hand test" and "Taber test" in Table 5 below.
[0150]
[0151] The enamel compositions of Examples 9 to 14 according to the present invention were obtained in the same manner as the above-mentioned compositions.
[0152] The mixture was screen printed on a Kerablack+ mother glass from Eurokera SNC and then fired at 930° C. by a ceramizing cycle to obtain a glass ceramic plate sample. The thickness of the deposit was then measured.
[0153] The wear test protocol is as follows:
[0154] Manual test: 1 ml of the product of the VitroClen brand from Reckitt Benckiser is applied to one point on the glass-ceramic sample to be tested. Cleaning is then simulated by rubbing back and forth 100 times over a distance of 10 cm using a sponge pad of Scotch Brite Blue sold by 3M. After cleaning, the test surface is wiped clean with a cloth and glass cleaner and the enamel wear is then evaluated by assigning the sample a comparative score of 0 to 5 relative to the original state of the enamel, where 0 means that the enamel is not damaged, 1 means particularly good wear resistance, 2 means good wear resistance, 3 means acceptable enamel wear, 4 means poor wear resistance and 5 means completely worn enamel.
[0155] Taber test: This test uses a Linear Abraser model sold by Taber, on which an 18 mm disc is mounted, equipped with a white Veraclen Critical Cleaning PL WIP 74603 cloth sold by Chicopee. The abraser is set to apply 5 N.cm to the disc. -2 The test surface is cleaned with a cloth and a glass cleaner, and the operator then evaluates the enamel wear by assigning a comparison score of 0 to 5 relative to the original state of the enamel to the sample, wherein 0 represents that the enamel is not damaged, 1 represents particularly good wear resistance, 2 represents good wear resistance, 3 represents acceptable enamel wear, 4 represents poor wear resistance, and 5 represents completely worn enamel.
[0156] It is evident from the above tests that the enamel composition according to the invention containing 20% by weight of talc, relative to the total weight of the enamel, has particularly satisfactory wear resistance.
[0157] Furthermore, comparison of the Taber test results of Examples 13 and 14 shows that the smaller the particle size of the glass frit used, the better the wear resistance of the resulting enamel.
Claims
1. An enamel composition for glass ceramic products comprising glass and talc.
2. The enamel composition according to claim 1, wherein talc is present in a proportion of 5 to 40% by weight, in particular 7 to 35% by weight, preferably 10 to 30% by weight, relative to the total weight of the enamel.
3. The enamel composition according to claim 1 , comprising less than 1% by weight of pigments, such as less than 0.5% by weight, in particular less than 0.1% by weight of pigments, relative to the total weight of the enamel, and the enamel is preferably free of pigments.
4. The enamel composition according to any one of the preceding claims, wherein the enamel is obtained from a mixture of glass frit and talc having a D90 of less than 20 μm, in particular less than 15 μm, preferably less than 10 μm.
5. The enamel composition according to any one of the preceding claims, wherein the glass has the following composition: SiO2: 35-50% B2O3: 23-30% Al2O3: 10-22% Li2O: 1-3% Na2O: 0-3% K2O: 2-5% Li2O+Na2O+K2O: <8% CaO: 1-5% CaO+MgO+ZnO+BaO+SrO: <7% TiO2: 0-2% ZrO2: 0-5% These proportions are expressed as weight percent relative to the total weight of the glass.
6. Enamel composition according to the preceding claim, wherein the glass has a thickness less than or equal to 60×10 -7 K -1 , especially less than or equal to 56×10 -7 K -1 The coefficient of thermal expansion.
7. The enamel composition according to any one of claims 5 or 6, wherein the glass has a softening point T above 650°C, in particular above 680°C. I .
8. The enamel composition according to any one of claims 5 to 7, comprising talc in a proportion of 15 to 40% by weight, in particular 17 to 35% by weight, preferably 20 to 30% by weight, relative to the total weight of the enamel.
9. The enamel composition according to any one of claims 1 to 4, wherein the glass has the following composition, these proportions being expressed as weight percentages relative to the total weight of the glass: SiO2 45-60%, preferably 50-58%, Al2O3 12-22%, preferably 15-19%, B2O3 12-22%, preferably 15-19%, Li2O 0-5%, preferably >0-5%, Na2O 0-2%, K2O>2%, CaO 0-4%, preferably 0-2%, MgO 0-4%, preferably >0-4%, ZnO 0-4%, preferably >0-4%, BaO 0-4%, preferably >0-4%, ZrO2 0-4%, especially 0-2%, preferably >0-2% TiO2 0-1%, preferably 0-0.5%, And the total proportion of oxides CaO+MgO+BaO+SrO+ZnO Less than or equal to 10%, preferably between 2% and 8%.
10. The enamel composition according to the preceding claim, comprising talc in a proportion of 5 to 30% by weight, in particular 7 to 20% by weight, relative to the total weight of the enamel, and the enamel preferably comprises talc in a proportion of 10 to 20% by weight.
11. A process for obtaining an enamel composition according to any one of the preceding claims, comprising mixing glass frit and talc, and optionally grinding the resulting mixture for a period of 5 minutes to 1 hour, in particular 15 minutes to 45 minutes, preferably 20 minutes to 40 minutes.
12. A glass ceramic article comprising at least one substrate, such as a glass ceramic plate, which substrate is at least partially coated with an enamel composition according to any one of claims 1 to 10.
13. A method for obtaining a glass product according to any one of the preceding claims, comprising: a. Provide glass ceramic substrate, b. printing on the substrate, in particular screen printing, the enamel composition according to any one of claims 1 to 10, and c. ceramicizing the combination of the substrate and the enamel, In particular, the ceramizing step comprises heating the combination of the substrate and the enamel at a temperature of 650° C. to 830° C., preferably for 5 to 90 minutes, and then at a temperature of 850° C. to 1100° C., preferably for 5 to 30 minutes.
Citation Information
Patent Citations
Thermally crystallizable glass, glass-ceramic made therefrom, and method of making same
EP0437228A1
Compositions pour revetement auto-nettoyant, notamment pour appareils menager de cuisson
FR2457312A1
Thermally crystallizable glass, glass-ceramic made therefrom, and method of making same.
FR2657079A1
Lead-free enamel compositions for the decoration of low-expansion glass-ceramics
FR2701473A1
Vitroceramic cooking surface provided with artificial intense black decorative effect obtained by firing decorative color including black pigment
FR2858974A1